2022
DOI: 10.2478/ffp-2022-0015
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of vascular plants in herb layers of ecotones in urban and non-urban forests in Brzesko city (Polish Carpathian foreland)

Abstract: Nowadays, human influence is more noticeable in urban and non-urban ecosystems, which, in turn, leads to the transformation of valuable natural resources. This article presents a study on the diversity of species composition of the vascular herb layer species of ecotones in selected urban forests of the city of Brzesko and in forests outside the city. All forests represented the association of oak–hornbeam plant. The results showed that there are inconsistent and consistent vascular plant species with the Tili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…The urban heat island has a negative impact on living organisms, including plants [3], as it increases their water demand [4] and reduces their drought resistance, which is common in the urban agglomerations of Poland. Studies have shown that the occurrence of the urban heat island phenomenon facilitates the development and expansion of species that do not belong to these habitats [5][6][7]. Roads are one of the main anthropogenic elements of the urban infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…The urban heat island has a negative impact on living organisms, including plants [3], as it increases their water demand [4] and reduces their drought resistance, which is common in the urban agglomerations of Poland. Studies have shown that the occurrence of the urban heat island phenomenon facilitates the development and expansion of species that do not belong to these habitats [5][6][7]. Roads are one of the main anthropogenic elements of the urban infrastructure.…”
Section: Introductionmentioning
confidence: 99%